Effect of Fluoride Varnish application on Primary Dentition among Preschool Children in Dharan: A Randomized Controlled Trial - Agrawal, Santosh Kumari; Shrestha, Ashish; Bhagat, Tarakant (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Topical application of fluoride varnish on the tooth surface prevents the dissolution rates of tooth materials and increases the re-precipitation of lost minerals. Objective: To assess the effectiveness of fluoride varnish application in primary dentition among preschool children at high risk of dental caries. Methods: A randomized controlled trial was conducted with two parallel-group, comprising 3–5-year-old children, 100 in each group (Fluoride varnish or Placebo varnish). Dental caries were recorded at baseline, three- and six-month using Caries Assessment and Treatment Instrument (CAST) scoring system. Statistical analysis was done using the Chi-square test for categorical data, Mann-Whitney U test, independent t-test, and Wilcoxon Signed Ranks test for quantitative data. The level of significance was set at p<0.05. Results: Overall, dental caries progression from baseline to three months and six months was more in placebo varnish group children than fluoride varnish (38.98% and 31.3% respectively). The proportion of children with new caries lesions was more in placebo group than that in the fluoride varnish group at every three months interval. The difference between the groups was statistically significant (p<0.05). Fluoride varnish treatment once in six months had a better treatment effect with a preventive fraction of 62.1% in comparison to three months (59.0%). Conclusions: Dental caries can be prevented effectively by the use of 5% sodium fluoride varnish. Fluoride varnish is efficacious when applied twice a year in children at high risk of dental caries.